Digitalization of intellectual activity in Russian regions - Evgeny V. Popov (Ural State University of Economics, 2020)
The article delves into the problems of the influence of digital technologies on intellectual performance. The relevance of the study is due to the fact that digital platforms underpin the innovative management mechanisms marked with a growing share of automation processes in the field of generation of knowledge and intellectual activity. One of such problems is the lack of unified methodological approaches to assessing the impact of digital technologies on intellectual performance. The methodological basis of the study includes strategic management theory and the principles of public and municipal governance. The research method is correlation analysis of the indicators of intellectual activity and the indicators of digital resources application. The information base of the research includes data on digital technologies application and the number of intellectual deliverables retrieved from the official website of the Federal State Statistics Service for the period of 2015–2017. Based on the theoretical analysis carried out, the authors conclude that the results of intellectual activity are the main tool for developing economic entities. We develop the weighted correlation coefficient of intellectual performance. This is an indicator that contains estimates of correlation coefficients of the results of intellectual activity and digital technologies, each of which has its own weighted coefficient. The study proves that digital technologies affect intellectual performance and their application increases the efficiency of intellectual activity.